2012
DOI: 10.1152/ajpheart.00606.2011
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in the intrinsic contractility of mesenteric collecting lymphatics in a rat model of metabolic syndrome

Abstract: Numerous studies on metabolic syndrome (MetSyn), a cluster of metabolic abnormalities, have demonstrated its profound impact on cardiovascular and blood microvascular health; however, the effects of MetSyn on lymphatic function are not well understood. We hypothesized that MetSyn would modulate lymphatic muscle activity and alter muscularized lymphatic function similar to the impairment of blood vessel function associated with MetSyn, particularly given the direct proximity of the lymphatics to the chronically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
83
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 77 publications
(107 reference statements)
15
83
2
1
Order By: Relevance
“…However, our results showing that injected insulin does not appear in the lymph of insulin-resistant muscle (10,28) could demonstrate that the lymph vessel itself suffers from dysfunction in insulinresistant muscle, and the similarities between blood and lymph vessels could support this argument. Thus, the ability of lymph to drain skeletal muscle interstitial fluid needs to be more fully investigated in both health and disease (52). However, since our insulin results are consistent with those of Szendroedi et al (45), and our FFA results are supported by both the absence of arterio-venous FFA difference and the time requirement for FFA incorporation into tissue (6,18), we believe that lymph is a good representation of the interstitial space in acute hyperlipidemia.…”
Section: Discussionsupporting
confidence: 80%
“…However, our results showing that injected insulin does not appear in the lymph of insulin-resistant muscle (10,28) could demonstrate that the lymph vessel itself suffers from dysfunction in insulinresistant muscle, and the similarities between blood and lymph vessels could support this argument. Thus, the ability of lymph to drain skeletal muscle interstitial fluid needs to be more fully investigated in both health and disease (52). However, since our insulin results are consistent with those of Szendroedi et al (45), and our FFA results are supported by both the absence of arterio-venous FFA difference and the time requirement for FFA incorporation into tissue (6,18), we believe that lymph is a good representation of the interstitial space in acute hyperlipidemia.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, Scallan and colleagues [35,36] reported that impaired nitric oxide signalling was responsible for lymphatic vascular disruption in type 2 diabetes and that the contractility of collecting lymphatic vessels was improved upon genetic deletion of basal nitric oxide synthase. Metabolic syndrome was also reported to contribute to the impairment of lymphatic contractility in rats fed a high-fructose diet [37]. In our study, in the absence of obesity, we found no major differences in the contractility parameters of the collecting lymphatic vessels upon HFD feeding, indicating that HFD without obesity is not sufficient to impair collecting lymphatic vessel function.…”
Section: Discussioncontrasting
confidence: 47%
“…12 A link between the metabolic syndrome and lymphedema was suggested by a study of rats fed a high fat diet that had significantly smaller diameter mesenteric lymphatic vessels, theoretically reducing their potential load capabilities and impairing the intrinsic contractility required for proper lymph flow. 24 Parallel to these animal studies, some clinical studies have also shown an association between obesity and lymphedema. A lymphoscintigraphy study of 15 obese patients with bilateral lower extremity enlargement and without a history primary lymphedema, inguinal lymphadenectomy, radiation, or ulceration of lower extremity showed that only 5 had abnormal results; these patients had a body mass index above 59.…”
Section: Discussionmentioning
confidence: 93%